Thomas De Quincey et la « vraie religion » - Frédéric Slaby (Revue Française de Civilisation Britannique)
According to De Quincey’s definition of religion, Christianity is not only a religion among others, but ‘a true religion’. Having no special attraction to the ‘Book of Nature’ which was privileged by Wordsworth, De Quincey turned to the Bible which he knew very well as a Protestant. Contrary to the first generation of English romantics such as Wordsworth and Coleridge in the Lyrical Ballads, De Quincey’s religious views thus remain within the bounds of Anglican orthodoxy.